Analysis on the space efficiency and environmental satisfaction in local government legislative buildings in Davao region - Quiñones, Jackie L. (2020)
As of present, there is a prevailing inefficient delivery of public service in offices that involves front line services. This is why the government has enacted the Republic Act No. 9485, otherwise known as the Anti-Red Tape Act of 2007.However, according to the Office of Government Commerce, Investment Property Databank on the year 2007, government offices are still occupied about 25% less efficiently. To address the problem of space efficiency, the study considered the physical constraints, operational constraints, and environmental perception of the users in order to gather results that will serve as basis for the planning and maximizing of space efficiency in the to-be proposed project.The researcher used Fuzzy Logic analysis to identify the efficiency percentage of each building considered in the study. This includes the New City Hall of Tagum, Panabo City Hall, Sangguniang Panlungsod ng Dabaw, andSangguniang Panlungsod ng Island Garden City of Samal. For the operational constraints, the researcher studied the Actual Time of Transaction as indicated in the Citizen?s Charter and conducted a survey whether or not this indicated time was followed. Lastly, the user perception was obtained by using the Perceived Environmental Quality (PEQ) Survey.Using the data obtained from the Fuzzy Logic analysis and survey, the researcher identified that most of the spaces provided in the current plan ofeach building is inadequate to cater the amount of people transacting inside the building. Furthermore, the lack of support facilities is evident in the absence of cafeterias and limited number of parking areas.With this, the researcher concluded that both the physical analysis of the building and user perception is necessary in order to establish a reliable basis of data that will be used to maximize space efficiency.